Fyodor Dostoevsky and Hieronymus Bosch: The Haywain in the Novel Crime and Punishment - Nikolay N. Podosokorsky (Достоевский и мировая культура: Филологический журнал)
The article compares the metaphysical works of Fyodor Dostoevsky and the Dutch artist Hieronymus Bosch (c. 1450–1516), who is famous for his depictions of surreal scenes of a world steeped in sin and filled with the most fantastic chimeras, often combining signs of the living and the inanimate. This characteristic of the artist immediately catches the eye when reading the first chapters of Crimes and Punishment, in which several characters are described through Raskolnikov’s painful perception in the spirit of Bosch’s hybrids. For example, it is noted that the thin and long neck of the old pawnbroker “looks like a chicken leg”; the face of the tavern owner, where the hero enters after making a “sample,” is described as “being as if oiled, like an iron lock” in Raskolnikov’s eyes, etc. Earlier, similar attempts to discover Boschian motifs in Russian literature of the 19th century were made by researchers based on the works of Alexandr Pushkin and Nikolay Gogol, but this is the first time that such a statement of the question has been made in relation to Dostoevsky in a dedicated article. In this study, we are not talking about any proven influence of Bosch on Dostoevsky, since it is unlikely (although not completely excluded) that the writer was even familiar with his paintings. The purpose of the study is to show using the novel Crime and Punishment and the Haywain Triptych that both Dostoevsky and Bosch, using pan-European Christian symbols and allegories, pointed in their works to a spiritual reality beyond time, which is unchangeable for people of different nations and epochs united by common ideas about the relationship between people and God and the devil and what happens to a person after he completely surrenders to the power of evil. The article analyzes in detail the concepts of “haywain” and “hay” in the novel in connection with Bosch’s triptych and reveals amazing similarities between the worlds of Dostoevsky and the Dutch visionary artist.